PENGARUH ANTE NATAL CARE (ANC) DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI MASA PANDEMI COVID-19 DI KABUPATEN KARAWANG TAHUN 2021 - Lilis Suryani; Rina Marlina; Maria Alia Rahayu (Fakultas Ilmu Kesehatan Unsika, 2023)
In Indonesia in 2011, the percentage of pregnant women with anemia with hemoglobin (Hb) levels below 11 g/dl was 30%, and Hb levels below 7 g/dl was 0.5% (1). Based on data from the Karawang District Service, in 2020 there were 8,020 cases of anemic pregnant women. With the COVID-19 pandemic, pregnant women have difficulty getting health services, especially routine checks to determine the condition of pregnancy, checking hemoglobin levels and there is a lack of health education about preventing anemia in pregnancy. So there is a need for an analysis of the condition of pregnant women's hemoglobin levels in the COVID-19 pandemic situation. Therefore, researchers conducted research entitled